2020
DOI: 10.1029/2020gl088010
|View full text |Cite
|
Sign up to set email alerts
|

Controls of Spring Persistence Barrier Strength in Different ENSO Regimes and Implications for 21st Century Changes

Abstract: This paper investigates potential factors that control the El Niño–Southern Oscillation (ENSO) Spring Persistence Barrier (SPB) strength in two different ENSO regimes and apply it to explain the ENSO SPB strength modulation after the 21st century. In a damped, noise‐driven model, the theoretical solution of SPB strength illustrates that a weaker ENSO growth rate strengthens SPB. In the self‐sustained regime, as in the Cane‐Zebiak model (chaotic system), the strengthened thermodynamic damping and weakened therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…For example, during 1980–1999, the ACC is about 0.6 at 12 months lag (blue line in Figure S7a in Supporting Information ), which is significantly higher than that after 2000 (blue line in Figure S7b in Supporting Information ). It is consistent with the previous findings that ENSO predictability decreases after 2000 (Jin et al., 2020; McPhaden, 2012). However, by decoupling SSS, the forecast skill drops dramatically during 1980–1999 at 12 months lag time (about 0.6 in blue line in Figure S7a vs. about 0.2 in red line in Figure S7a in Supporting Information ), which suggests that SSS plays an important role in ENSO prediction.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…For example, during 1980–1999, the ACC is about 0.6 at 12 months lag (blue line in Figure S7a in Supporting Information ), which is significantly higher than that after 2000 (blue line in Figure S7b in Supporting Information ). It is consistent with the previous findings that ENSO predictability decreases after 2000 (Jin et al., 2020; McPhaden, 2012). However, by decoupling SSS, the forecast skill drops dramatically during 1980–1999 at 12 months lag time (about 0.6 in blue line in Figure S7a vs. about 0.2 in red line in Figure S7a in Supporting Information ), which suggests that SSS plays an important role in ENSO prediction.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…One possible reason that leads to this SPB is the specific initial errors in the tropical Pacific (Mu, Duan, & Wang, 2007, 2007b). However, recent studies have identified numerically and analytically that the seasonally varying background of the tropical Pacific may be an important factor in causing the SPB (Y. Jin et al., 2019, 2020, 2021; Y. Jin and Liu, 2021a, b; A. F. Levine and McPhaden, 2015; Liu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, accurate simulation and prediction of ENSO one or more seasons in advance is of great importance. However, one significant obstacle in ENSO prediction is the spring predictability barrier (SPB), which consists of a dramatic drop in forecast skill when the prediction is made through spring (Z. Hou et al., 2018; Jin et al., 2008, 2019, 2020; Webster & Yang, 1992; Wu et al., 2009; Xue et al., 1994). One possible reason that leads to this SPB is the specific initial errors in the tropical Pacific (Mu, Duan, & Wang, 2007, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…However, accurate ENSO forecasts several seasons in advance are still challenging (e.g., Tang et al., 2018). One significant obstacle in ENSO prediction is the so‐called “spring predictability barrier” (SPB), which consists of a dramatic drop in forecast skill when the numerical ENSO predictions are made through spring (e.g., Hou et al., 2019; Jin et al., 2008, 2019, 2020; Webster & Yang, 1992; Wu et al., 2009; Xue et al., 1994). The SPB is also known as the strong error growth in the boreal spring (Duan & Hu, 2016; Duan & Mu, 2018; Mu et al., 2007; Tao et al., 2019).…”
Section: Introductionmentioning
confidence: 99%